APPLIED QUALITY FUNCTION DEPLOYMENT (QFD) FOR ELONGATED CHAIR DESIGN - Mukhtar, M. Nushron Ali (UNIPA PRESS, 2019)
In line with the times, the need for product development ideas has a high selling value. Economic value and product efficiency are highly considered in the design, one of which is the design of a stall or café chair. In general, the most used seats are permanent. In other words, it can't adjust when used for a few people or for a lot of people. Therefore it is necessary to design stalls and café chairs that can be stretched or shortened automatically. The purpose of designing this elongated chair is, it can be arranged so that it can be shortened, with this advantage we can save space and expand the space and of course it will be designed according to consumer needs. The elongated chair is made using the Quality Function Deployment (QFD) method. Some methods that must be done, namely the Voice of Customer collection phase, which is done by distributing questionnaires to 25 respondents. The next step is House of Quality based on the results of the questionnaire. After the HOQ is completed, then the analysis and implementation phase of the results obtained at HOQ will be applied to the product design.